1996
DOI: 10.1159/000237410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Antigens on Eosinophils from Patients with Eosinophilia

Abstract: Recent studies have suggested that there may be heterogeneity among human eosinophils. To study this further, surface antigens on blood eosinophils from patients with eosinophilia (23 bronchial asthma, 6 eosinophilic pneumonia, 1 Kimura’s disease and 1 adult T-cell leukemia) and from 8 control subjects were examined using a new direct method for fluorescence detection of eosinophils. HLA-DR+ and CD4+ eosinophil counts were higher in patients with bronchial asthma and adult T-cell leukemia (ATL) than in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is up-regulated to a greater degree (1.5-1.8-fold by CF or about threefold by intensity) on BAL [63,100,117,118,164,171] and sputum (up to 18-fold) [119,120] eosinophils. However, blood eosinophil a M level is not significantly different among patients with mild and severe asthma, and normal subjects [77,112,119,125,161]. a X is increased (1.8-fold by intensity) on BAL [118] and (about threefold) on sputum [120] eosinophils but was found not to be different between subjects with asthma or airway allergy and normal subjects [77].…”
Section: Integrinsmentioning
confidence: 84%
See 3 more Smart Citations
“…It is up-regulated to a greater degree (1.5-1.8-fold by CF or about threefold by intensity) on BAL [63,100,117,118,164,171] and sputum (up to 18-fold) [119,120] eosinophils. However, blood eosinophil a M level is not significantly different among patients with mild and severe asthma, and normal subjects [77,112,119,125,161]. a X is increased (1.8-fold by intensity) on BAL [118] and (about threefold) on sputum [120] eosinophils but was found not to be different between subjects with asthma or airway allergy and normal subjects [77].…”
Section: Integrinsmentioning
confidence: 84%
“…These include CD9, whose expression on blood eosinophils from subjects with allergic rhinitis and occasional asthma was found to be higher during a high pollen load season (1.2-fold by fluorescence intensity) [170] but was in another study not different between subjects with asthma or airway allergy and normal subjects [77]. CD45RO expression on blood eosinophils is higher in patients with mild-moderate asthma than in normals (about 65% positive cells versus 5%) [125]. CD48 on blood eosinophils is up-regulated by IL-3 (about twofold by intensity), but not by IL-5 or GM-CSF, and is higher in patients with asthma (twofold) than in normal subjects [199].…”
Section: Othersmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, marked expression of activation and adhesion molecules (CD45RO, CD18, CD11b) was detected on eosinophils in both patients, at diagnosis. Increased expression of CD45RO, CD11b has also been demonstrated to be suggestive of eosinophil activation in patients with asthma and allergic conditions (Thorne et al 1990;Yachie et al 1993;Sakamoto et al 1996). It has been shown that CD11b and CD18 play a role in migration of activated eosinophils to the site of allergic in¯ammation and in eosinophil adhesion to endothelial cells (Walsh 1997a;Yachie et al 1993 3 ).…”
Section: Discussionmentioning
confidence: 99%